TINJAUAN YURIDIS DEWAN PERWAKILAN DAERAH DALAM MEMBUAT KEBIJAKAN NEGARA - Aspani, Budi; Yusmanda, Riza (Faculty of Law, University of Palembang, 2022)
The formation of the Regional Representative Council was decided in the third Amendment to the 1945 Constitution. This accommodates aspirations and gives the regions a greater role in decision-making processes that are directly related to the region. This study discusses the authority of the Regional Representatives Council only to participate in discussing certain Draft Laws related to regional autonomy and can give consideration to the House of Representatives when exercising its authority. The role of the Regional Representative Council in the decision-making process on State policies. Implicitly the Regional Representative Council as a state legislative institution is very limited, namely only proposing and discussing and not as a breaker like the People's Representative Council.